ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA PADA PELAKSANAAN PROGRAM PENGALAMAN LAPANGAN (PPL) - Astuti; Sitti Mania; Nur Khalisah Latuconsina; Sri Sulasteri; Nur Miftahul Jannah (Al Asma: Journal of Islamic Education, 2022)
The purpose of this study was to determine the basic teaching skills of PPL students majoring in mathematics education in implementing the field experience program (PPL). This type of research is descriptive research with a qualitative approach. The research was conducted at MTs Madani Alauddin with subjects consisting of 6 students from class of 2014 Mathematics Education Study Program. Data collection was carried out using observation, interview, and documentation techniques. The data is then grouped into primary data and secondary data. Primary data comes from observations and interviews, while secondary data is obtained from documentation studies. The results showed that mathematics education students had fairly good skills in terms of opening lessons, explaining, asking questions, giving reinforcement, making variations, managing classes, guiding discussions, and closing lessons. However, in a number of indicators, students' mathematics education is not optimal, such as attracting attention, giving references/instructions, carrying out variations on teaching methods and variations on tools, attracting the use of methods and mastery of competencies, dividing attention, and evaluating indicators. There are several indicators that are not optimal because student knowledge about the 8 indicators of basic teaching skills is still lacking and preparation is not mature enough.